OH···O and OH···S intramolecular interactions in simple resonance-assisted hydrogen bond systems: a comparative study of various models - Nowroozi, A.; Hajiabadi, H.; Akbari, F. (Structural chemistry, 2014)
The energy of intramolecular hydrogen bond (IMHB) is a central subject in chemistry and biochemistry. In contrast with the IMHBs, there is no general accepted procedure to determine the IMHB energy. In the present study, for the first time, we applied all the different adopted models for assessing the energy of IMHB of O–H···O and O–H···S in simple resonance-assisted hydrogen bond systems (the cis enol form of malonaldehyde, thiomalonaldehyde, and a variety of halogenated derivatives), and compared them. The energy of IMHB, by various methods such as related rotamers method (RRM), rotational barrier method (RBM), conformational analysis method (CAM), isodesmic reaction method (IRM), and open–close method (OCM), was estimated. Exploring and comparing the correlations between the IMHB energies with various descriptors of hydrogen bond strength, such as geometrical, topological, molecular orbital, and spectroscopic parameters, were carried out. According to the theoretical results, we found that both RRM and RBM have the best linear correlations with all of the hydrogen bond descriptors ( R ≥ 0.90) while the results of other methods (CAM, IRM and OCM) are not suitable ( R ≤ 0.80). Surprisingly, we found that the OCM, which has been widely applied in the estimation of the IMHB energy, has the weakest linear dependent with all of the HB descriptors. Consequently, according to the regression coefficients, the order of linearity of these methods is as follows: RRM > RBM > > CAM > IRM > OCM.